Extensive Gene Amplification as a Mechanism for Piperacillin-Tazobactam Resistance in Escherichia coli - Lisa M. Schechter (American Society for Microbiology, 2018)
ABSTRACT Although the TEM-1 β-lactamase (BlaTEM-1) hydrolyzes penicillins and narrow-spectrum cephalosporins, organisms expressing this enzyme are typically susceptible to β-lactam/β-lactamase inhibitor combinations such as piperacillin-tazobactam (TZP). However, our previous work led to the discovery of 28 clinical isolates of Escherichia coli resistant to TZP that contained only blaTEM-1. One of these isolates, E. coli 907355, was investigated further in this study. E. coli 907355 exhibited significantly higher β-lactamase activity and BlaTEM-1 protein levels when grown in the presence of subinhibitory concentrations of TZP. A corresponding TZP-dependent increase in blaTEM-1 copy number was also observed, with as many as 113 copies of the gene detected per cell. These results suggest that TZP treatment promotes an increase in blaTEM-1 gene dosage, allowing BlaTEM-1 to reach high enough levels to overcome inactivation by the available tazobactam in the culture. To better understand the nature of the blaTEM-1 copy number proliferation, whole-genome sequence (WGS) analysis was performed on E. coli 907355 in the absence and presence of TZP. The WGS data revealed that the blaTEM-1 gene is located in a 10-kb genomic resistance module (GRM) that contains multiple resistance genes and mobile genetic elements. The GRM was found to be tandemly repeated at least 5 times within a p1ESCUM/p1ECUMN-like plasmid when bacteria were grown in the presence of TZP. IMPORTANCE Understanding how bacteria acquire resistance to antibiotics is essential for treating infected patients effectively, as well as preventing the spread of resistant organisms. In this study, a clinical isolate of E. coli was identified that dedicated more than 15% of its genome toward tandem amplification of a ~10-kb resistance module, allowing it to escape antibiotic-mediated killing. Our research is significant in that it provides one possible explanation for clinical isolates that exhibit discordant behavior when tested for antibiotic resistance by different phenotypic methods. Our research also shows that GRM amplification is difficult to detect by short-read WGS technologies. Analysis of raw long-read sequence data was required to confirm GRM amplification as a mechanism of antibiotic resistance.